Kreatifitas Pengolahan Melinjo (Gnetum Gnemon) Menjadi Emping dengan Memanfaatkan Media Sosial sebagai Alat Promosi Penjualannya dan Sosialisasi Pencatatan Keuangan Sederhana - Denny Kurniawan; Ani Ratmayanib; Irna Maya Sari (Universitas Pamulang, 2021)
UMKM are a potential business for economic development in Indonesia so that in practice it is necessary to optimize and explore the existing potentials to increase community economic development. In Perumasan Village, Kalanganyar Sub-District, Takakan District, Serang City. Banten, there are many UMKM with potential, one of which is Emping Melinjo UMKM. Emping Melinjo is a food made from saplings. When viewed from a quantity perspective, there are quite a lot of tanks in the Perumasan village, this is what encourages Emping melinjo UMKM to have promising business potential, at least to help the economy of the surrounding community. The problem is that UMKM lack knowledge regarding digital marketing and there is no management of financial Statement. The results of this community service activity are providing training and assistance related to digital marketing using Whatsaap, Instagram, Marketplace, and making simple financial report logbooks